SOME ASPECTS OF PRAWN CULTURE IN THE SEASONAL AND PERENNIAL FIELDS OF VYPEEN ISLAND - George, K V (Indian Journal of Fisheries, 2011)
Prawn culture is extensively practised in the paddy fields (seasonal fields)and other low lying areas (perennial fields) of Vypeen Island. Though theseasonal fields are found to be more productive, the perennial fields, which areavailable for prawn culture throughout the year, are not less important. Prawnsstay for longer time and attains larger size in this type of fields. The averageannual production of prawns is 903.3 and 838.6 kg|ha in the seasonal and perennialfields respectively. The month-wise catch rates show that higher catchrate is generally observed in January-iMarch period. Four species of penaeidprawns, Metapenaeus dobsoni, M. monoceros, Penaeus indicus and P. monodonconstitute the culture fishery of which M. dobsoni contributes more than 50% ofthe catch. It is observed that M. dobsoni in the perennial fields grow at an averagerate of 10.0 mm per month. Although, the total expenditure to run the seasonalfield is higher than that of the perennial fields, the net income realisedfrom the seasonal field is always found to be better. It is therefore concludedthat the paddy field prawn culture is more profitable than the culture of prawnsin perennial fields.